Depression Is Associated With High Levels of C-Reactive Protein and Low Levels of Fractional Exhaled Nitric Oxide: Results From the 2007-2012 National Health and Nutrition Examination Surveys - Cepeda, M Soledad; Stang, Paul; Makadia, Rupa (The journal of clinical psychiatry, 2016)
Major depressive disorder may be due to psychoneuroimmunological dysfunction, as studies have documented increased levels of a variety of inflammatory mediators in depressed subjects. Nitric oxide (NO) is marker of inflammation, and fractional exhaled NO (FeNO) is a marker of airway inflammation. Plasma NO and FeNO levels have been shown to be lower in subjects with depression in small studies. We sought to assess the association of depression with C-reactive protein (CRP) and FeNO levels in a large and representative sample of the US population. Population-based cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES). NHANES collects health information about the US population through interviews, medical examinations, and laboratory tests. We included subjects ≥ 20 years old who participated in NHANES in 2007 to 2012, responded to the depression questions, and had CRP values or ≥ 2 reproducible FeNO measures. Depression was measured using the 9-item Patient Health Questionnaire (PHQ-9). Subjects were classified as depressed if PHQ-9 scores were ≥ 10. FeNO and CRP levels were log transformed. Unadjusted and adjusted regression analyses were conducted. A total of 14,276 subjects responded to the PHQ-9, and 7.73% had depressive symptoms. Of these subjects, 10,036 had CRP values and 12,513 had FeNO measurements. Subjects with depressive symptoms had, after adjustment, CRP levels that were 31% higher (95% confidence interval [CI], 14% to 50%) and FeNO levels that were 10.7% lower (95% CI, -2.5% to -17.1%) than in subjects with no depressive symptoms. Depression is associated with high CRP levels and low FeNO levels. Of importance, this study (1) assesses the association of depression with CRP and exhaled NO levels in a large and representative sample of the US population, (2) contributes to the neuroimmunological dimension of depression, (3) confirms the association of depression with high levels of CRP, and (4) assesses, for the first time, the association of depression with peripheral NO in more than 10,000 subjects from the general population.